Bibliometric Analysis of the Impact of Government Policies on Sustainable Agriculture Business in the Context of Sustainability - Judijanto, Loso; Chatra, Afdhal; Rahayu, Silvia; Putra, Trimardi Jaya (West Science Interdisciplinary Studies, 2023)
This paper conducts a comprehensive bibliometric analysis to explore the evolving landscape of sustainable agriculture business in the context of government policies. The study delves into the multifaceted realm of agribusiness, examining its global significance, economic impacts, and the challenges it faces, particularly in the transition to Agriculture 4.0. The paper highlights the intricate relationship between government policies and the sustainability of agriculture businesses, addressing barriers, technological advancements, and the growing complexity of global agri-food systems. Notably, the implications for practitioners, policymakers, and researchers are elucidated, offering strategic insights for each stakeholder group. The research aims to answer three fundamental questions: the classification of existing research, identification of research trends, and the exploration of potential future research opportunities. Employing bibliometric techniques, the study presents a mapping of terms, overlay visualizations, and density visualizations to unravel the interconnectedness of research clusters and their temporal evolution. Additionally, the paper identifies the most highly cited articles and explores the thematic priorities within the discourse on sustainable agriculture and farm-related issues. Comparative analyses with previous studies in related domains contribute to a deeper understanding of the current research landscape. The findings provide actionable insights for practitioners, inform evidence-based policymaking, and guide future research endeavors in the dynamic field of sustainable agriculture business.